Rethinking the stock market participation puzzle: A qualitative approach - Kamila Duraj; Daniela Grunow; Michael Chaliasos; Christine Laudenbach; Stephan Siegel (Goethe University Frankfurt, Institute for Monetary and Financial Stability (IMFS), 2024)
We revisit the limited stock market participation puzzle leveraging a qualitative research approach that is commonly used in many social sciences, but much less so in finance or economics. We conduct in-depth interviews of stock market participants and non-participants in Germany, a high-income country with a low stock market participation rate. Differently from a survey using preset questions based on theory, we elicit views in an open-ended discussion, which starts with a general question about "money", is not flagged as regarding stock market participation, and allows for probing and follow-up questions. Many of the factors proposed by the literature are mentioned by interviewees. However, non-investors perceive surprisingly high entry and participation costs due to a fundamental misunderstanding of the potential for selecting "good" stocks and avoiding "bad" ones and for market timing through frequent trading. Surprisingly, the investors we interview often share these views. However, they find a way to overcome these costs with the help of family, friends, or financial advisors they trust. While the insights from our qualitative interviews are based on a small number of interviewees, we find consistent evidence in a population-wide survey of investors and non-investors.
Keywords: 330